Tiltrotor whirl flutter analysis in support of NGCTR aeroelastic wind tunnel model design - Cocco, A.; Masarati, P.; Hoff, S. van 't (My University, 2021)
This work presents the modeling and preliminary whirl-flutter stability results achieved within the Advanced Testbed for TILtrotor Aeroelastics (ATTILA) CleanSky2 project. ATTILA entails the design, manufacturing and testing of a semi-span wind tunnel model of the Next Generation Civil TiltRotor. A description of the preliminary MBDyn and FLIGHTLAB multibody models is presented. The modelling technique of each subcomponent of the model, namely the wing, the rotor, the blades and the yoke is briefly illustrated. The predicted dynamic characteristics of the wing-pylon system and the rotor are then compared. Finally, some preliminary whirl-flutter stability predictions are presented, along with the techniques that will also be used in the wind tunnel tests to identify the aeroelastic modes of the model.